1997
DOI: 10.1007/s002329900183
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cDNA/Protein Leading to an Increased P i -uptake in Xenopus laevis Oocytes

Abstract: In a previous report we documented an increased Na(+)-dependent transport of inorganic phosphate (P(i)) in Xenopus laevis oocytes injected with mRNA isolated from rabbit duodenum (Yagci et al., Pfluegers Arch. 422:211-216, 1992; ref 24). In the present study we have used expression cloning in oocytes to search for the cDNA/mRNA involved in this effect. The identified cDNA (provisionally named PiUS; for P(i)-uptake stimulator) lead to a 3-4-fold stimulation of Na(+)-dependent P(i)-uptake (10ng cRNA injected, 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 0 publications
4
44
1
Order By: Relevance
“…2), similar to the apparent molecular weight of about 60 kDa reported for PiUS [13]. This enzyme preparation was tested for kinase activity against some of its possible substrates.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…2), similar to the apparent molecular weight of about 60 kDa reported for PiUS [13]. This enzyme preparation was tested for kinase activity against some of its possible substrates.…”
Section: Resultsmentioning
confidence: 69%
“…The a¤nity of the enzyme for InsP 6 is lower than that of the enzyme puri¢ed from brain by Voglmaier et al [10] (their reported K m was 0.7 þ 0.192 WM). However, as with the Ins-(1,4,5)P 3 3-kinases [3], it may be that a brain-speci¢c isoform exists and given that the source of PiUS is an intestinal epethlial library [13], we are most likely studying an enzyme from peripheral tissue.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IP6K2 gene was cloned almost 20 years ago, while searching for a novel mammalian intestinal phosphate transporter and was identified as PiUS (Phosphate inorganic Uptake Stimulator) [59]. When PiUS RNA was injected into Xenopus oocytes, it stimulated the cellular uptake of radioactive phosphate.…”
Section: Inositol Pyrophosphates As Metabolic Regulatorsmentioning
confidence: 99%